2013
DOI: 10.1016/j.amj.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Activation Intervals for a Helicopter Emergency Medical Service in Japan

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the future electronic transfer of measurements could be used to reduce typing errors, however, this does not eliminate the errors in measurement per se. The rate of cancelled or denied missions in the Finnish HEMS system is substantially higher than reported elsewhere [6,7,21,22]. Technical reliability of the service seems to be excellent and it contributed to the cancellation rate minimally.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…In the future electronic transfer of measurements could be used to reduce typing errors, however, this does not eliminate the errors in measurement per se. The rate of cancelled or denied missions in the Finnish HEMS system is substantially higher than reported elsewhere [6,7,21,22]. Technical reliability of the service seems to be excellent and it contributed to the cancellation rate minimally.…”
Section: Discussionmentioning
confidence: 62%
“…Key findings of this study were that in the Finnish HEMS system a large proportion of missions are cancelled or denied, and a relatively small percentage of patients are transported by helicopter. We also found that the medical problem for HEMS dispatch differ from comparable systems [7,8,21].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations